Nasoalveolar Molding In Unilateral Cleft Lip and Palate: Two Case Reports - Arzu Arı-Demirkaya; Toros Alcan; Serkan Sağır; Özhan Çelebiler (Galenos Yayinevi, 2008)
Nasoalveolar molding is a method which aims to decrease the severity of the deformity of infants with cleft lip and palate before primary repair. Using this method, alveolar segments adjacent to the cleft can be approximated, while a symmetrical archform can be achieved by using tissue expansion principles. Also, alar dome cartilages and columella can be lifted by taking advantage of the malleability of the immature cartilage. In this report, treatment details of two infants with different types of unilateral cleft and the results after primary lip repair will be presented.